Case report: Hereditary spastic paraplegia with a novel homozygous mutation in ZFYVE26 - Lai, Ze-hua; Liu, Xiao-ying; Song, Yuan-yue; Zhou, Hai-yan; Zeng, Li-li (Frontiers in Neurology, 2023)
Hereditary spastic paraplegia (HSP) is a group of neurodegenerative diseases with genetic and clinical heterogeneity characterized by lower limbs spasticity and weakness. It includes four genetic inheritance forms, autosomal dominant inheritance (AD), autosomal recessive inheritance (AR), Xlinked inheritance and mitochondrial inheritance. Until now, more than 82 gene loci have been found to cause HSP, and SPG15 (ZFYVE26) is one of the most common ARHSPs with thin corpus callosum (TCC), presents with early cognitive impairment and slowly progressive leg weakness.Here we reported a homozygous pathogenic variant in ZFYVE26. A 19-year-old Chinese girl was [在此处键入] admitted to our hospital, because of a 2-year progressive bilateral leg spasticity and weakness, early cognitive impairment; corpus callosum dysplasia; chronic neurogenic injury of the medulla oblongata supplied muscles and bilateral upper and lower limbs on electromyogram (EMG). Based on these clinical and electrophysiological features, HSP was suspected. Exome sequencing of the family was performed by high-throughput sequencing, and analysis of the patient shows a ZFYVE26 NM_015346: c.7111dupA p.(M2371Nfs*51) homozygous mutation. This case reported a new ZFYVE26 pathogenic variant, which was different from SPG15 gene mutation reported before.